Por uma Rabat biofílica: a vegetação urbana como elemento estruturador de uma paisagem salutogênica - ecopositiva e biofílica - Simone Marques de Sousa Safe (2024)
Over the last 50 years, man has extensively modified ecosystems, of which the degradation of environmental services is one of the consequences with significant damage to human well-being and loss of natural heritage. Global commitments seek to reverse the damage caused by climate change, which involves the loss of biodiversity and alterations to ecosystem services through significant regional and global political and institutional changes. The research aims to investigate environmental services in conjunction with individual values through supportive, regulatory and cultural ecosystem services. The discussion permeates urban planning in its environmental and human aspects, based on an understanding of the importance of nature for the urban environment and for life. The objective of study is to analyze the landscape of the capital Rabat, which has a significant presence of natural elements in its infrastructure. Understanding the Kingdom of Morocco's governance mechanisms made it possible to identify a direction towards the need to include the thematic axis of health and well-being. Investigating biophilic design offers a perspective for urban planning, with a proactive and salutogenic approach, rather than a conventional reactive and pathogenic approach. The inclusion of biophilic indicators generates greater equity in natural, visible and accessible systems through vegetated public spaces. Its conceptual support is based on Evidence-based design studies and biophilic indicators, whose interactions with the natural environment can reduce stress, irritability, mental fatigue, blood pressure and aggressiveness, as well as promoting positive results in behavior, self-esteem and mood. As a methodology, the pedagogical process is proposed in order to generate evidence: to study people's ability to perceive the restorative value of the natural environment, their connection with nature and the biophilic quality of the environment. Field research was conducted with students from the School of Architecture at the International University of Rabat over five semesters between 2021 and 2022. Other methodological procedures such as remote sensing and data geoprocessing supported the analysis of ecosystem service provision (especially carbon flow) and landscape metrics from the perspective of landscape ecology, and overlapped with biophilic indicators, carried out at multiple scales - from the region to the public open space. As a contribution, the research highlights Rabat's potential as the first biophilic city in Africa and as part of an international network, as well as promoting the applicability of the indicators in a practical case, serving as inspiration for the Brazilian reality (South America could be part of the biophilic network in the future).